Study on the impact of climate risk on the agricultural insurance purchasing behavior of herding households—an empirical analysis based on Inner Mongolia - Chen, Xiao-long; Zhao, Yuan-feng (Frontiers in Sustainable Food Systems, 2024)
The analysis of herding households’ agricultural insurance purchasing behavior under climate risk can help improve the agricultural insurance system in pastoral areas in China.By constructing an analytical framework of “climate change, risk perception, and herding households’ agricultural insurance purchase decisions,” this study matched the survey data from 764 herding households across different types of grasslands in Inner Mongolia with meteorological data from 2019 to 2023. Based on Probit model regression and mediation effect tests, the following conclusions were drawn: Firstly, climate change, especially abnormal fluctuations in precipitation, triggers yield losses and induces loss aversion among herding households, which translates into agricultural insurance purchasing behavior. Secondly, as herding households are divided into production herding households and subsistence herding households, the impact of climate risk on production herding households’ agricultural insurance purchase decisions is more pronounced than that of subsistence herding households. Thirdly, from the perspective of the mechanism of climate change on the agricultural insurance purchasing behavior of production-oriented herding households, climate risk mainly influences herding households’ agricultural insurance purchase through their risk perception. Therefore, with the intensification of global climate change, while further stimulating the agricultural insurance purchasing demand of living herding households through differentiated premium subsidy policies in the future, it is necessary to further enhance the risk perception level of herding households by strengthening the construction of weather forecasting and agricultural and livestock risk data sharing platform, so as to transform the external changes in climate risk into the intrinsic motivation of herding households’ agricultural insurance purchasing behaviors, and to enhance the herding households’ Climate risk coping capacity of herdsmen.